Khatam Al-Quran in Islamic education curriculum in Malaysia - Hassan, Surul Shahbudin; Zailaini, Muhammad Azhar (Elsevier, 2013)
This study intends to explore the role played by J-QAF and Islam Education teachers in achieving the objective of complete recitation of the Quran (Khatam al-Quran) by primary school pupils. The study is focussed on teachers involved in the teaching of J-QAF first level pupils in 2005, now in their fourth year of primary school. The teachers involved have used the best possible strategy and technique in their lessons in order to ensure that Muslims pupils would be able to accomplish Khatam al-Quran while at primary school. Among fourth year pupils, there are some who have achieved complete recitation. However, this has been accomplished through a combination of the pupils’ recitation at home as well as in school. Although some pupils have completed, there are still (many) pupils at the level of Iqra’ books 1, 2 and 3. So this study is intended to discover the reality of the teaching of J-QAF since it was introduced in 2005.